MEASURING THE EFFECTIVENESS OF AI-SUPPORTED DIGITAL LEARNING PLATFORMS: EVIDENCE FROM CYBERLEARN HUB IMPLEMENTATION - Muhammad, Roziyaliney; Hasan, Haris Fadillah; Razali, Fatimah Zahra W (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
This study examines the effectiveness of CyberLearn Hub, an AI-supported e-learning platform integrated with CyberBuddy chatbot assistance, in enhancing students’ learning experience in cybersecurity education. A quantitative research design was employed, and data were collected from respondents using a structured questionnaire. The analysis was conducted using SPSS, including descriptive statistics, reliability analyses, Pearson correlations, and multiple regression. The findings demonstrate that the overall regression model is statistically robust and possesses substantial explanatory power in explaining variations in learning efficiency. System use performance was identified as the most significant factor, followed by AI chatbot effectiveness, indicating the importance of usability and intelligent support in digital learning environments. While user engagement demonstrated a moderate effect, usage acceptance showed no statistically meaningful impact on learning effectiveness. The study demonstrates the importance of integrating AI technologies with user-centered design in improving e-learning outcomes. The findings provide practical implications for educators and developers in designing effective AI-enhanced learning systems, particularly in technical domains such as cybersecurity.